Evaluation and Prevention of Hydrogen Embrittlement by NDT Methods: A Review - Sujeet Choudhary; Manish Vishwakarma; Sandeep Kumar Dwivedi (Materials Proceedings, 2021)
This paper comprises of hydrogen embrittlement phenomena in material, factors responsible for the hydrogen embrittlement and non-destructive methods to evaluate the internal defect in machines or components when working in hydrogen atmosphere. Hydrogen embrittlement is responsible for sub-critical crack growth in materials, fracture and mechanical properties such as ductility, toughness, and consequently loss of strength. This hydrogen is induced into the material during electrochemical reactions and in a high-pressure hydrogen gas environment. The paper covers the review on the capabilities of non-destructive testing methods regarding advantages and disadvantages. Sometimes one non-destructive technique does not provide sufficient information about physical integrity and therefore a different combination of methods is required. Ultrasonic testing is very useful to detect internal defects.